A study on a U-shaped piezoelectric coupled beam and its corresponding ingenious harvester. (15th October 2019) - Hu, Xiaobin; Li, Ying; Xie, Xiangdong
Abstract: In order to harvest ambient renewable or recovery energy, a novel piezoelectric energy harvester which mainly includes vibrators, a rotor and a cylindrical outer casing is presented in this paper. The vibrator is made of a U-shaped bimorph piezoelectric beam with a magnet slab mounted on its free end, and the rotor is a disc with magnet slabs embedded in the grooves along its periphery. The theoretical analysis model of the harvester is established and the mechanical and electrical responses are obtained. The results indicate that the harvester can achieve a maximum response by adjusting the rotor speed to make it work near resonance. As the beam section width or the substrate thickness decreases, or the piezoelectric patch thickness increases, the effective power of the harvester generally increases. On the whole, the substrate thickness has the greatest influence on the responses of the harvester, the piezoelectric patch thickness follows, and the influence of the beam section width is the smallest. In particular, the electric power generated from the harvester can reach 8.19 KW by adjusting the values of the related design parameters, which is comparable to a traditional small windmill generator, and therefore the proposed harvester has an appealing application prospect. Highlights: A novel piezoelectric energy harvester made of U-shaped beams is developed. A theoretical model is established to calculate the charge and voltage generated from the harvester. The effects of a variety of design parameters on the response of the harvester are studied. An electric power up to 8.19 KW can be generated by the novel piezoelectric harvester with a radius of 0.5 m.